Comparative in Vitro Evaluation of Cardioprotective, Antioxidant, Anti-Inflammatory, and Anti-Apoptotic Activities of Commercial Herbal Cocktail Supplements - Pankaj Mohan Pimpalshende; Stuti Verma; Jeevanandham Somasundaram; Manisha S. Nangude; Sai Koteswar Sarma; Km Reena; Sandip Narendrabhai Badeliya; Aitilaris Nongsiej (The Bioscan, 2026)
Cardiovascular diseases (CVDs) are the most common causes of death all over the world and this requires the constant investigation of preventive and curative measures. The worldwide prevalence of CVDs, which are stimulated by such factors as oxidative stress, inflammation, and cardiac cell death through apoptosis, has prompted interest in complementary and alternative medicine. The potentials of herbal medicines due to their historical background and multi-target characteristics present an opportunity. These include commercially available herbal cocktail supplements that are a mixture of a few allegedly cardioprotective herbs such as Hawthorn, Garlic and Turmeric, which have received considerable consumer popularity. The effectiveness of these complex mixtures is, however, not always scientifically proven, and there is urgent need to compare them to support the claims of the manufacturer. This study was aimed at carrying out a comparative in vitro assessment of the cardioprotective ability of three commercially prepared brands of herbal cocktail mixtures (named Brand A, B, and C). The approach was multi-faceted in nature with the phytochemical analysis commencing with determining the total phenolic (TPC) and flavonoid (TFC) content through aqueous extracts. This was done with a battery of important assays to measure in vitro antioxidant ability (DPPH, FRAP, ABTS), anti-inflammatory ability through TNF-a and IL-6 inhibition amid LPS-instigated macrophages model, and direct cardioprotective/anti-apoptotic impact on H2O2-induced oxidative stress cardio myoblast cells of the H9c2 rat. The key findings in the summary showed that there was a strong pecking order among the brands. Brand A displayed better performance, containing the highest TPC and TFC, the strongest antioxidant activity (lowest IC50 in DPPH assay), the strongest inhibition of the pro-inflammatory cytokines, and the strongest ability to protect the H2O2-induced cytotoxicity and pro-inflammatory ability of H2O2 on H9c2 cells. Brand B was moderately active in all assays whereas Brand C always produced the most weak effects. The phytochemical content and the observed biological activities were shown by a strong positive correlation. The key finding is that the formulation of Brand A has the most extensive in vitro cardioprotective profile, which can probably be explained by the more diverse phytochemical profile. This research has a far-reaching implication since it implies that there is a high degree of variability in the efficacy of commercial herbal products and it forms a scientific foundation allowing the consumer and the health care practitioner to select evidence-based formulations. It highlights the need to ensure that there is standardized quality control and strict scientific validation of the nutraceutical industry. Keywords Lumbar spine; Vertebral morphometry; CT scan; Age variation; Spinal biomechanics; Surgical planning